Frailty – Prediction of disability in activities of daily living and instrumental activities of daily living in a two year follow-up - Domingues, Bruno (2015)
Frailty is a state of increased vulnerability, which entails a high risk of impairment and disability. There is currently no consensus regarding the characterization of frailty, but in a more current perspective, developed by Gobbens, frailty is defined as a dynamic state that affects the individual who experiences loss in one or more domains (physical, psychological and/ or social). To examine how frailty contributes to the prediction of disability in activities daily living (ADL) and instrumental activities of daily living (IADL) in a two year follow-up in a sample of community-dwelling elderly.